When open access might not work: Understanding patient attitudes in appointment scheduling. Issue 4 (October 2018) - Finkelstein, Stacey R.; Liu, Nan; Rosenthal, David; Poghosyan, Lusine
Abstract : Background: Open-access (OA) systems aim to reduce delays to care. However, recent evidence suggests that OA systems might reduce patient satisfaction and result in poorer patient experiences due to patients' inability to obtain appointments with their usual care provider. We conducted a series of experiments to explore the role of risk attitudes, an individual difference variable that measures preferences for risky options, in patients' perception of OA systems. Purpose: The aim of the study was to investigate the relationship between patient's risk attitudes and attitudes toward OA systems and demonstrate whether patients' attitudes toward OA systems will vary as a function of their risk attitudes. Methodology: Three separate experiments were conducted to assess the relationship between patient risk attitudes and their attitudes about OA systems. Study 1 (patient population) explored the aforementioned relationship. We explored two potential moderators for this effect: how salient the tradeoff is between delays to care and quality of care (Study 2; online population) and the severity of the patient's health condition (Study 3; patient population). Results: Compared to risk-averse patients, risk-seeking patients have more favorable attitudes toward OA systems (a 1-point increase in risk attitudes on a 7-point scale resulted in a 0.44-point boost in attitudes toward OA systems on a 7-point scale). This relationship holds even when the tradeoff between access to care and quality of care is made salient (e.g., a practice informs patients they can have a same-day appointment but are unlikely to see their regular provider) and when people consider having a minor health condition. This relationship is attenuated when patients imagine having a serious medical condition because speedy access to care becomes a top priority. Conclusion: Risk-seeking patients have more favorable attitudes toward OA systems. Practice Implications: Risk-seeking patients are primarily driven by speed to access at the potential expense of continuity of care. Organizations that better understand patient motives in scheduling medical appointments can introduce more effective interventions and positively impact patient experiences of care.